Oncolytic herpes simplex virus-based strategies: toward a breakthrough in glioblastoma therapy - Ning, Jianfang; Wakimoto, Hiroaki (Frontiers in Microbiology, 2014)
Oncolytic viruses are a class of antitumor agents that selectively kill tumor cells while sparing normal cells. Oncolytic herpes simplex virus (oHSV) has been investigated in clinical trials for patients with the malignant brain tumor glioblastoma for more than a decade. These clinical studies have shown the safety of oHSV administration to the human brain, however, therapeutic efficacy of oHSV as a single treatment remains unsatisfactory. Factors that could hamper the anti-glioblastoma efficacy of oHSV include: attenuated potency of oHSV due to deletion or mutation of viral genes involved in virulence, restricted viral replication and spread within the tumor; suboptimal oHSV delivery associated with intratumoral injection; virus infection-induced inflammatory and cellular immune responses which could inhibit oHSV replication and promote its clearance; lack of effective incorporation of oHSV into standard-of-care, and poor knowledge about the ability of oHSV to target glioblastoma stem cells (GSCs). In an attempt to address these issues, recent research efforts have been directed at: (1) design of new engineered viruses to enhance potency, (2) better understanding of the role of the cellular immunity elicited by oHSV infection of tumors, (3) combinatorial strategies with different antitumor agents with a mechanistic rationale, (4) “armed” viruses expressing therapeutic transgenes, (5) use of GSC-derived models in oHSV evaluation, and (6) combinations of these. In this review, we will describe the current status of oHSV clinical trials for glioblastoma, and discuss recent research advances and future directions toward successful oHSV-based therapy of glioblastoma.